Peningkatan Keterampilan Guru IPA dalam Mengembangkan Media Pembelajaran Inovatif Berbasis Potensi Lokal - Ade Suryanda; Eka Putri Azrai; Daniar Setyorini (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Science learning media is an inseparable part of a learning process. The achievement of learning indicators made by a teacher, in addition to being determined by teaching skills and mastering the material, also determined learning media. These community service activities are based on the fact that teachers generally still have difficulties in developing learning media that are simple, inexpensive and can stimulate student involvement. The purpose of this activity is to provide teachers with the tools to develop innovative and challenging science learning media that are in accordance with the 21th century character. This training uses experiential learning methods with participant-centered approach through case study techniques, and simulations, followed by the process of making learning media simple. The resulting output target is the ability to develop innovative and simple science learning media.